Contemporary Risk Stratification of Acute Coronary Syndrome - Gurleen Kaur; Swati Chand; Devesh Rai; Bipul Baibhav; Ron Blankstein; Debabrata Mukherjee; Phillip Levy; Martha Gulati (US Cardiology Review)
Chest pain is one of the most common presenting concerns of patients seeking care in the emergency department, and the underlying etiology can range from acute coronary syndrome to various other non-cardiac causes. Initial evaluation should focus on characterizing symptoms and identifying risk factors, but further risk stratification using clinical decision pathways and biomarkers (cardiac troponin) is essential. The 2021 American Heart Association/American College of Cardiology guidelines for the evaluation and diagnosis of chest pain represent the first ever guidelines for the evaluation of patients with acute chest pain. The contemporary risk stratification methods described in these guidelines allow for the identification of patient subgroups: patients who do not require further testing, patients who should proceed directly to the cath lab, and patients who will benefit from further anatomic or functional testing. In this review, we describe contemporary risk stratification methods for acute coronary syndrome and summarize the recommendations put forth by the guidelines.